A Comparison of Three Different Treatment Regimens of HCV Infection in295 Iraqi Patients - Jasim, Wasan Khraibet; Firhan AL-Khalid, Nawal M.; Hussei, Ahmed A. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Viral Hepatitis C infection is global public health problem throughout the world. Different treatment regimens are used which produce different rates of response affected by many factors. Objectives: To assess the efficacy of three different treatment regimens in 295 Iraqi patients infected with chronic HCV. Patients and methods: This is an observational cohort study; in which 295 (133 male and 162 female) patients with chronic HCV infection were enrolled during the period between August 2015 to January 2017 from Gastroenterology clinic of Baghdad Teaching Hospital and Gastroenterology and Hepatology Teaching Hospital. Baseline HCV viral load measurements and genotyping were done for each patient. Patients were followed up by viral load measurement at end of the treatment period and three months after the end of the treatment. Results: The majority of patients infected with chronic HCV achieved sustained virological response(SVR) (defined as undetectable HCV RNA 12 to 24 weeks after the end of the treatment); were of the generic( sofosbuvir/ledipasvir) treatment group (51out of 72 (70.8% ) followed by generic Sofosbuvir with (peg interferon/ribavirin)treatment group (68 out of 111 (61.3%) followed by (peg interferon/ribavirin) treatment group (42 out of 86 ( 48.8%). Conclusions: The best treatment efficacy was obtained with generic sofosbuvir/ledipasvir followed by sofosbuvir with peg interferon and ribavirin then peg interferon and ribavirin. The most responder genotype in Iraqi patients was genotype 4 and the least responder genotype was genotype 1b